Kajian Terhadap Makna “Boboso” Dalam Tradisi Lisan Masyarakat Maluku Utara Dalam Perspektif Analisis Pragmatics Kritis - Djafar, Hariyanti; Ismail, Julia (Peneliti.net, 2023)
Boboso is part of an oral tradition that is still frequently used and trusted for its truth among rural and urban communities in North Maluku province. Boboso, which usually begins with the words